Effect of Low-Dose Hormone Therapy on Metabolic Parameters and Bone Mineral Density - Ufuk Atlihan; Onur Yavuz; Huseyin Aytug Avsar; Can Ata; Tevfik Berk Bildaci; Selcuk Erkilinc (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Early menopause causes several health concerns that are related directly to the deficiency of ovarian hormones, especially estrogen insufficiency. The purpose of the research was to investigate the impact of low-dose hormone therapy on metabolic parameters and bone densitometry in patients with early menopause.